Acanthosis nigricans in childhood: A cutaneous marker that should not be underestimated, especially in obese children. (14th October 2019) - Maguolo, Alice; Maffeis, Claudio
Abstract: Aim: The occurrence of acanthosis nigricans (AN) in childhood should not be underestimated since it acts as a cutaneous marker of underlying diseases, such as insulin resistance, endocrinopathy, syndromes and malignancy. The purpose of this review was to highlight the clinical significance of AN in childhood and draw attention to its possible role as early marker of alterations in glucose metabolism in obese children. Methods: The Cochrane Library and PubMed databases were searched for papers published in English up to April 2019. Observational studies, case reports and reviews from 1994 to 2019 were included. Results: Most of the cases of AN are associated with obesity. The prevalence of obesity is rising worldwide and is paralleled by global increases in the prevalence of metabolic syndrome in children. Insulin resistance and AN are closely associated. Evidence indicates that AN is a useful clinical marker for the identification of obese and overweight children and adolescents with insulin resistance who are susceptible to type 2 diabetes mellitus and metabolic syndrome. Conclusion: In clinical practice, the recognition of AN is useful for an early identification of children and adolescents, prone to the insulin‐resistant obese phenotype, who could benefit from early interventions.